Macro level drivers of globalization in Indian and Chinese service organizations: an empirical study - Ananthram, Subramaniam; Pearson, Cecil (Montclair State University, 2007)
Cross-border trade across disappearing geographic boundaries has been the most important factor that has led to the intensification of economic globalization in the past two decades. Major political, legal and economic reform measures at the national level have been the driving force for economic globalization across developed and developing countries across the globe. In the services industry, generally, reforms at the national level include government controlled deregulation of industries, foreign investment allowances and licencing. These government led reforms have been pivotal towards the global resurgence in the demand and provision of services across the global marketplace. It is contended in this paper that there are three other forces, besides 'government' enablers that are necessitating these changes at the national level. These forces are 'market', 'cost', and competition. Collectively, these four forces shape globalization. The impact and importance of these forces was examined with data that were obtained from a study with indigenous managers employed in the service industry in China (n = 210) and India (n = 239). Employing a pluralist (quantitative and qualitative procedures) design, the data reveal market forces were of the most overall importance in both nations. However, for different service sectors, the impact and intenstity of the principal force varied. Experimental evidence obtained from indigenous service industy managers in India and China through qualitative focus groups and one-on-one interviews are utilized to explain and justify the quantitative rankings in the discussion section. Further, the implications of the findings for global business are elucidated in the concluding section.